Assessing Psychometric Properties of the Italian Version of the Heartland Forgiveness Scale - Consoli, Simone; Rossi, Alessandro; Thompson, Laura Y.; Volpi, Clarissa; Mannarini, Stefania; Castelnuovo, Gianluca; Molinari, Enrico (Frontiers in Psychology, 2020)
Despite increasing popularity and intensive worldwide use, few studies have assessed the validity and factorial structure of the Heartland Forgiveness Scale (HFS). However, scientific literature showed that the original factorial structure of the HFS was not fully replicated and – in addition – the Italian translation is still lacking. To fill this gap, this study aims to extend evidence about the original HFS factorial validity by analyzing the Italian version. The final sample was composed of 523 randomly enrolled participants [139 males (26.6%), 384 females (73.4%)] aged from 18 to 82 years (mean = 42.53, SD = 16.41) who completed the Italian version of the HFS. The confirmatory factor analysis (CFA) showed good fit indices for the original hierarchical factor solution and a significant decrease in model fit was found for all of the competing models. Also, the Italian version of the HFS revealed good reliability and very good psychometrical properties. Findings suggest that the Italian version of the HFS can be considered a reliable and good psychometrically-based instrument for the assessment of dispositional forgiveness of the Self, Other, and Situation.